An Analysis of Discrepancy between the Lesson Plan and the Implementation of Curriculum 2013 in Teaching and Learning Process in SD Negeri 4 Kaliuntu - Jayanta, I Nyoman Laba; Suryantari, Kadek Dewi; Sumantri, Made (LPPM Undiksha, 2017)
This research aimed to determine how large the discrepancy between the ideal condition and the implementation of 2013 curriculum in teaching and learning process in SD Negeri 4 Kaliuntu reviewed from the lesson plan and teaching learning process. This research was evaluative research which apply discrepancy model. Measurement of the program effectiveness was done by comparing the ideal conditions, based on Permendikbud No. 103 of 2014, with the real conditions on the implementation of 2013 Curriculum at SD Negeri 4 Kaliuntu. Lesson plan data, was measured by the study documentation methode. Meanwhile, the teaching and learning process data was measured by observation methode. Subject of this research consisted of 6 teachers of SD Negeri 4 Kaliuntu. The data scores was form for all variables were analyzed by using the Wilcoxon’s signed rank test. The sign difference and score difference were calculated with a predetermined standard. The result of the analysis indicate that the large of discrepancy between ideal conditions (based on Permendikbud No. 103 of 2014) and the implementation of 2013 Curriculum in SD Negeri 4 Kaliuntu in terms of lesson plan is 12,17%. The discrepancy lies on indicators of learning activities, assessment of learning result, media and learning resources. Reviewed from the teaching learning process, the discrepancy occurs at 19.17%. The discrepancy occurs in the indicator of giving apperception, convey of evaluation techniques that will be used by teachers, students are directed reflection of the activities that have been implemented, and the provision of follow-up by giving remedial, enrichment, or giving assignments.